A CNOT gate between multiphoton qubits encoded in two cavities - S. Rosenblum; Y. Y. Gao; P. Reinhold; C. Wang; C. J. Axline; L. Frunzio; S. M. Girvin; Liang Jiang; M. Mirrahimi; M. H. Devoret; R. J. Schoelkopf (Nature Communications, 2018)
Quantum computing platforms allowing quantum error correction usually rely on complex redundant encoding within multiple two-level systems. Here, instead, the authors realize a CNOT gate between two qubits encoded in the multiphoton states of two microwave cavities nonlinearly coupled by a transmon.